Listening to Stakeholders: Agricultural research and Rural Radio Linkages - Hambly Odame, Helen; Kassam, A. (International Service for National Agricultural Research, 2002)
In October 2000, ISNAR, along with partners in Africa and Canada, initiated a project to investigate the linkages between agricultural research and rural radio. This project was concerned with developing a working relationship between researchers and broadcasters to ensure a two-way exchange of knowledge with farmers. The study initially focused on sub-Saharan Africa. This Briefing Paper serves to highlight results from the study's training needs and organizational constraints assessment (TNA) workshop held in March 2001 in Ghana. The top two training priorities that emerged were facilitating partnerships between research and radio, and mobilizing financial resources for collaborative activities.